Which processes dominate visual search: Bottom-up feature contrast, top-down tuning or trial history? - Becker, Stefanie I.; Grubert, Anna; Horstmann, Gernot; Ansorge, Ulrich (Cognition, 2023)
Previous research has identified three mechanisms that guide visual attention: bottom-up feature contrasts, top-down tuning, and the trial history (e.g., priming effects). However, only few studies have simultaneously examined all three mechanisms. Hence, it is currently unclear how they interact or which mechanisms dominate over others. With respect to local feature contrasts, it has been claimed that a pop-out target can only be selected immediately in dense displays when the target has a high local feature contrast, but not when the displays are sparse, which leads to an inverse set-size effect. The present study critically evaluated this view by systematically varying local feature contrasts (i.e., set size), top-down knowledge, and the trial history in pop-out search. We used eye tracking to distinguish between early selection and later identification-related processes. The results revealed that early visual selection was mainly dominated by top-down knowledge and the trial history: When attention was biased to the target feature, either by valid pre-cueing (top-down) or automatic priming, the target could be localised immediately, regardless of display density. Bottom-up feature contrasts only modulated selection when the target was unknown and attention was biased to the non-targets. We also replicated the often-reported finding of reliable feature contrast effects in the mean RTs, but showed that these were due to later, target identification processes (e.g., in the target dwell times). Thus, contrary to the prevalent view, bottom-up feature contrasts in dense displays do not seem to directly guide attention, but only facilitate nontarget rejection, probably by facilitating nontarget grouping.